Social Anxiety as Predictor of Depression in Adolescents: Mediating Role of Dysfunctional Daydreaming - Shafiq, Sameera; Zafar, Hajra (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: To investigate the relationship among Dysfunctional Daydreaming, Social Anxiety and Depression in adolescents and explore the mediating role of daydreaming between two variables. METHODOLOGY: Cross-sectional correlational research design was conducted to collect data from 200 participants (Males=94, Females=106) of age range 12 to 19 years (M=17.08, SD= 1.93) with a convenient sampling technique via google form due to COVID-19 during the lockdown period April to June 2020. Inclusion criteria focused on willing participants who were studying online during the pandemic. Unwilling students, along with the freezing of study, were excluded. Three standardized questionnaires, Patient Health Questionnaire (PHQ-9) for measuring Depression, the Social Anxiety Scale for Adolescents (SAS-A) for measuring Social Anxiety and Dysfunctional Daydreaming Scale (DDS) for measuring malfunctioning fantasies, were used. The demographic sheet and informed consent form were filled out correctly to administer the questionnaires. Data were analyzed in SPSS-24 for frequencies, percentages, and correlations. Mediation analysis was conducted in AMOS-24. RESULTS: Pearson Product Moment Correlation Coefficient revealed a positive correlation of Dysfunctional Daydreaming with Social anxiety (r=.50, p<0.05) and Depression (r=0.58, p<0.05). Dysfunctional daydreaming mediated between social anxiety and Depression in adolescents (?=0.34, p<0.05). CONCLUSION: The research indicated social support as a predictor of Depression in adolescents with a strengthening impact of abnormal Daydreaming on Depression. An implication for mindfulness interventions that focus on the present moment without judgment is necessary to regulate anxiety, Depression, and daydreaming in college students. KEYWORDS: Dysfunctional Daydreaming, Depression, Social Anxiety.